The Implementation of Panca Jiwa in Pesantren Agro Nur El Falah Salatiga - Nugroho, Haryo Aji; Makarim, Winarno Bassam; Anindi, Rizki Parahita (UIN Walisongo Semarang, 2021)
The purpose of this study is to describe the implementation of panca jiwa (five spirit) of Agro Nur El Falah Islamic boarding school in Salatiga. The data is collected through observation, interview and document. The analysis technique used is descriptive qualitative. The results of this studies are; that the concept of the panca jiwa of the pesantren includes sincerity, self-awareness, simplicity, exemplary, compassion, which is contained in the values of Indonesian character education: hard work, religious, honest, disciplined, independent, curiosity, creative, respect for achievement, social care, responsible, democratic, caring for the environment, peace-loving, friendly or communicative, and tolerant. Panca Jiwa are the guidelines in the daily activities of the students in this pesantren. It has been conveyed by the guardian of pesantren in ceremonies, public lectures, MOS, and others. In fact, there are still many students who make fun of their friends, fight, steal belongings of friends, avoid school, violate regulations, and even commit serious violations which result in being expelled from pesantren. There are several factors that may hinder the implementation of panca jiwa, such as the lack of cooperation between the teachers in supervising the students, the lack of activities that can make the students become families to each other, the infrastructure is damaged and not immediately handled and also their personalities at home. There must be real examples from both teachers and senior santri (students) about how to behave based on panca jiwa. Therefore, cooperation from teachers is needed to be more diligent in directing, guiding, educating and supervising the students to achieve the desired goals in accordance with the vision and mission of this pesantren